Prophylactic clip application for large pedunculated polyps before snare polypectomy may decrease immediate postpolypectomy bleeding - Soh, Jae Seung (BMC Gastroenterol, 2020)
BACKGROUND: Although prophylactic clip application before polypectomy may prevent postpolypectomy bleeding (PPB), the usefulness of prophylactic clipping in the treatment of large pedunculated polyps is controversial in some prospective randomized studies. This study was conducted to evaluate the efficacy of prophylactic clip application and to investigate the predictors of PPB in large pedunculated colorectal polyps. METHODS: A total of 137 pedunculated polyps (size ≥1 cm) in 116 patients were prospectively included and randomized into group A (with clipping) and group B (without clipping), and resected. The occurrences of immediate PPB (graded 1–4) and delayed PPB were compared. RESULTS: Sixty-seven polyps were allocated in group A and 70 polyps in group B. In both groups, the median polyp diameter was 15 mm (P = 0.173) and the median stalk diameter was 3 mm (P = 0.362). Twenty-eight (20.4%) immediate PPB episodes in 137 polyps occurred, 6 (9.0%) in group A and 22 (31.4%) in group B (P = 0.001). However, the occurrence of delayed PPB was not different between the groups (P = 0.943). Prophylactic clip application decreased the occurrence of immediate PPB (odds ratio 0.215, 95% confidence interval 0.081–0.571). Moreover, polyp size ≥20 mm and stalk diameter ≥ 4 mm increased the risk of immediate PPB. CONCLUSIONS: Clip application before polypectomy of ≥1 cm pedunculated polyps is effective in decreasing the occurrence of immediate PPB. Thus, clip application should be considered before performing snare polypectomy, especially for large polyps with a thick stalk. TRIAL REGISTRATION: This research was studied a prospective maneuver and enrolled in a registry of clinical trials run by United States National Library of Medicine at the National Institutes of Health (ClinicalTrials.gov Protocol Registration and Results system ID: NCT01437631). This study was registered on September 19, 2011.